Diversity of birds on a floodplain island in the Middle Solimões, Tefé, Amazonas, Brazil - de Castro, Renilce Carvalho; Bernhard, Rafael; Lima, Ana Caroline Gomes de (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2024)
Birds stand out for their performance in aiding the ecological balance, as they act by pollinating flowers, dispersing seeds and controlling pests in plantations. Although they are a group considered to be the best studied, in the Amazon, studies in the floodplain are scarce compared to those on dry land. Thus, the objective of this research was to know the diversity of bird species that occur on a floodplain island in the Middle Solimões, as well as to identify and quantify the species found in the environment of the riverside community and in the floodplain forest. Therefore, data collection took place by direct observation with binoculars, recording of vocalization and photographs of the birds, at fixed points. Species were recorded using a field book and identified by consulting the list of local birds, field guides, and by consultations with specialists in the field of ornithological. Data were analyzed by the rarefaction curve using the EstimateS 9.1 program. A total of 82 bird species were recorded, where the community environment had the highest dominance and the closed forest had the highest species richness. This research contributed to the increase in the number of species recorded in the municipality, as well as in the areas of Amazonian floodplains.
Keywords: Avifauna; Middle Solimões; Floodplain island; Thicket. Community